Economic Transformation in Djibouti : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2019)
The purpose of this Systematic Country Diagnostic (SCD) is to identify the most critical development constraints facing Djibouti and how to make growth more inclusive and sustainable while promoting shared prosperity. The findings and recommendations of the SCD are based on analytical work carried out by a World Bank Group team with expertise in macroeconomics and poverty analytics, human capital development and labor markets, infrastructure and private sector development, governance and climate change. The team also undertook consultations with the Government of Djibouti and representatives from civil society, private sector stakeholders and the donor community. The SCD provides analysis and recommendations for policies that the Government might pursue to reduce barriers to inclusive and sustainable growth and achieve its vision of becoming a modern economy and regional hub for trade and logistics, which can create jobs and raise living standards for Djiboutians.